Creating visions for university-school partnerships - Ferrara, JoAnne, 1955-; Nath, Janice L.; Guadarrama, Irma N. (Research in professional school development., 2014)
In keeping with the tradition set forth in volumes 1-4, this fifth volume, Creating Visions for University- School Partnerships: A Volume in Professional Development School Research, continues to exemplify current thinking of practitioners and researchers in the field. The range of authors from the Prek-16 arena illustrates the ways in which professional development schools generate possible solutions to the complex problems facing educators. The diversity of their work represents perspectives of classroom teachers, preservice teachers, school leaders, and university faculty who grapple with identifying 'ways of knowing' and 'ways of doing' that enhance educational outcomes for Prek-12 students while also serving to transform the profession. The volume's contents of 19 chapters divided into four areas: (1) Clinically Rich Practices (2) PDS Stakeholders' Perspectives (3) Enriching Content Area Instruction (4) Family Engagement, gives us a more vivid picture of the work that partnerships are doing to fulfill the PDS promise for improving teaching and learning at every level.